Antibiofilm efficacy and genomic characterization of a lytic bacteriophage targeting MDR uropathogenic Escherichia coli - Muhammad Hassan; Iqbal Ahmad Alvi; Sadiq Noor Khan; Dawood Ahmed; Muhammad Asif; Afshan Saleem; Abdul Jabbar (Archives of Microbiology, 2026)

Optogenetic Pacemaker Cells for Biological Cardiac Rhythm Management in Sick Sinus Syndrome - Versha Devi; Syeda Aliza Aamir; Syed Abdullah Shah; Muhammad Dawood Ghaffar; Muhammad Talha; Muneeb Saifullah (Cell Biochemistry and Biophysics, 2026)

Ethnobotany of desert medicinal plants and their sustainable ethnomedicinal utilization - Salman Majeed; Muhammad Zafar; Sayyara Ibadullayeva; Nahaa M Alotaibi; Sheikh Zain Ul Abidin; Muhammad Rizwan Khan; Sumreen Dawood; Khuzin Dinislam; Adnan Amin (The Science of Nature, 2026)

Machine Learning and Deep Learning for Snowmelt Prediction: Long-Term Trends and Implications for Water Resource Management - Dawood Ahmad; Muhammad Haseeb (Water Resources Management, 2026)

Advances in Coated Fertilizers for Sustainable Agriculture - Muhammad Tahir Murad; Sadia Murad; Waqar Akram; Mohammad Shafiq u Rahman; Afroz Rais; Abdul Qadir; Dawood Atta (Journal of Soil Science and Plant Nutrition, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

Stem anatomical microcharacters and morphology as diagnostic botanical markers in Euphorbiaceae species - Sehrish Rubab; Salman Majeed; Sumreen Dawood; Muhammad Zafar; Modhi O. Alotaibi; Sayyara Ibadullayeva; Fakhra Bibi; Yusra Khan; Adnan Amin (The Science of Nature, 2026)

GC-MS Profiling, Cytotoxicity and Antiviral Activity of Caulerpa lentillifera and C. macrodisca from Northern Coastal Waters of Borneo Island, Eastern Malaysia - Mohammad Tamrin Mohamad Lal; Elden Sai Long Chang; Zy Chee Wong; Leong Seng Lim; Muhammad Dawood Shah; Wahidatul Husna Zuldin; Gilbert Ringgit; Nur Azreen Arbi; Ahmad Hazim Abdul Aziz; Abdul Aziz Jaziri; Asep Awaludin Prihanto; Attabik Mukhamad Amrillah; et al. (Marine Biotechnology, 2026)

Exploring the efficacy of a novel cannabidiol and bevacizumab combination in non-small cell lung cancer - Abdul Qadir; Zurqa Khalid; Ayesha Kashmala Ghauri; Muhammad Hamza Dawood; Usama Manzoor; Habib Ur Rehman (DARU Journal of Pharmaceutical Sciences, 2026)

Etlingera Species of Borneo's wild gingers: traditional knowledge, phytochemistry, and modern applications - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Shafiquzzaman Siddiquee (Phytochemistry Reviews, 2026)

Harnessing traditional ethnoveterinary practices and medicinal plants for sustainable livestock health in arid rangelands - Shumaila Batool; Murad Muhammad; Minahal Fatima; Muhammad Waheed; Muqadas Batool; Mona F. A. Dawood; Abdul Wahab; Abdul Waheed; Khalid Abbas (Genetic Resources and Crop Evolution, 2025)

Distribution patterns and controlling factors of cave saltpeter around the Sichuan Basin, China - Shi Chen; FuDong Wang; Yuyin Zhu; Carlos Pérez-Mejías; Wuyang He; Qinyingzi Cai; Dawood Muhammad; Xueqin Zhao (Carbonates and Evaporites, 2025)

YOLOv5 Revisited: A Lightweight yet Accurate Framework for Plant Disease Detection in Agricultural Applications - Huria Ali; Muhammad Imran; Saad Irfan Khan; Anees Tariq; Hassan Dawood; Hussain Dawood (Applied Fruit Science, 2025)

Climate damage resilience: how fiscal decentralization, environmental and economic factors shape the climate - Fayaz Hussain Tunio; Agha Amad Nabi; Zhao Rui Feng; Radulescu Magdalena; Muhammad Dawood (Environment, Development and Sustainability, 2025)

Characterisation of the gut microbiome and surveillance of antibiotic resistance genes in green sea turtles (Chelonia mydas) - Dawood Ghafoor; Orachun Hayakijkosol; Noppadol Prasetsincharoen; Carla C.M. Chen; Muhammad Noman; Poommate Chomchat; Robert Kinobe (Marine Environmental Research, 2025)

Next-generation strategies for nitrogen-efficient maize production for a greener tomorrow - Muhammad Faheem Jan; Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Dawood Ahmadzai; Asia Maqbool; Faheem Shehzad Baloch; Ming Li (Field Crops Research, 2025)

Metabolite profiling and antipathogenic properties of Rhizophora mucronata against marine leech Pterobdella arugamensis and Vibrio species in hybrid grouper - Fui Jin Wong; Wei Sheng Chong; Yoong Soon Yong; Jen Kit Tan; Rossita Shapawi; Muhammad Dawood Shah (Aquaculture International, 2025)

Quantitative exploration and conservation of the medicinal plant resources used by the inhabitants of Northern Pakistan - Murad Muhammad; Abdul Waheed; Abdul Wahab; Nimrah Ameen; Ibad Ullah; Muhammad Majeed; Muhammad Waheed; Khalid Rehman Hakeem; Mona F. A. Dawood; Wen-Jun Li (Genetic Resources and Crop Evolution, 2025)

Cytotoxicity of Physalis minima Linn (Solanaceae) fruit against HCT116 and HT29 colorectal cancer cell lines - Wei Lun Ng; Jen Kit Tan; Charles Gnanaraj; Muhammad Dawood Shah; Nurshamimi Nor Rashid; Iskandar Abdullah; Yoong Soon Yong (Natural Product Research, 2025)

Root Diameter-Associated Exudates Drive the Changes in Rhizosphere Microbial communities - Huabo Du; Butian Wang; Muhammad Dawood; Peng Qu; Weifeng Li; Lingyan Zhang; Syed Asad Hussain Bukhari; Xuedong Shi; Meijun Qi; Shilang Dong; Yu Ge (Journal of Soil Science and Plant Nutrition, 2025)

Syringic Acid in Canarium odontophyllum for Diabetes and Obesity – A Review - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Noor Atiqah Aizan Abdul Kadir; Shafiquzzaman Siddiquee (Cell Biochemistry and Biophysics, 2025)

Retraction notice to “Biodiesel synthesis from Prunus bokhariensis non-edible seed oil by using green silver oxide nanocatalyst” [Chemosphere 291, Part 2, March 2022, 132780] - Sumreen Dawood; Mushtaq Ahmad; Muhammad Zafar; Saira Asif; Jiří Jaromír Klemeš; Awais Bokhari; Muhammad Mubashir; Ning Han; Mohamed M. Ibrahim; Zeinhom M. El-Bahy; Kuan Shiong Khoo (Chemosphere, 2025)

Phosphorus Application Improved Grain Yield, Phosphorus Use Efficiency and Economic Returns of Different Pearl Millet Genotypes Grown on Alkaline Soil - Abdul Majeed; Muhammad Bahram Khan; Ahmad Dawood; Yasir Mehmood; Sami Ul-Allah; Mubshar Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Factors governing bark tufa deposition in fluvial systems: the case study of Nuorilang in Jiuzhaigou, Sichuan China - JunHao Li; FuDong Wang; WuYang He; QinYingZi Cai; Shi Chen; GuoQing Huang; Dawood Muhammad; Carlos Pérez-Mejías; Rui Zhang; ZiTong Peng; SiRui Chen; ChenWei Ji; et al. (Carbonates and Evaporites, 2025)

Effects of dietary vitamins C and E on growth performance, hematological and biochemical parameters, skeletal abnormalities, and disease resistance against V. harveyi of hybrid groupers (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂) - Isabella Ebi; Rossita Shapawi; Leong-Seng Lim; Annita Seok-Kian Yong; Nurzafirah Mazlan; Muhammad Dawood Shah; Najamuddin Abdul Basri; Abdul Aziz Jaziri (Aquaculture International, 2025)

Reassessing China's virtual water trade with a global value chain framework: Participation, inequality and multi-scenario analysis - Ziyi Wei; Zhongci Deng; Muhammad Dawood; Yajuan Yu; Zhen Wang; Kai Huang (Resources, Conservation and Recycling, 2025)

Evaluation of Microplastics Ingested by Sea Cucumber Holothuria Scabra from Pulau Jambongan, Sabah - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Vijay Kumar Subbiah; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Audrey Daning Tuzan; Sitti Raehanah Muhammad Shaleh; Norfazreena Mohd Faudzi; Rossita Shapawi; Muhammad Dawood Shah; Tze Young Thung (Bulletin of Environmental Contamination and Toxicology, 2025)

Development of growth curve and estimation of genetic parameters of Nili-Ravi buffalo calves from birth to one year of age through non-linear models - Asad Abbas; Atia Basheer; Moinina Nelphson Kallon; Numan Sharif; Heydar Ghiasi; Tariq Mehmood; Burhane Azam; Anjum Khalique; Muhammad Dawood; Imran Zahoor (Tropical Animal Health and Production, 2024)

LC-MS/MS profiling of the poisonous wild mushroom, Entoloma mastoideum, (Entolomataceae, Basidiomycota) in Sabah (Northern Borneo), Malaysia - Ily Azzedine Alaia M.H. Subari; Gowri Mutthumanickam; Muhammad Hj. Jikal; Muhammad Dawood Shah; Jen Kit Tan; Yee Shin Tan; Praneetha Palasubermaniam; Kishneth Palaniveloo; Jaya Seelan Sathiya Seelan (Toxicon, 2024)

The urban-rural dietary water footprint and its inequality in China's urban agglomerations - Tang Tan; Linxiu Wu; Zhongci Deng; Muhammad Dawood; Yajuan Yu; Zhen Wang; Kai Huang (Science of The Total Environment, 2024)

Phenols, flavonoids and anthocyanins in Solanum lasiocarpum from Borneo: In vitro antioxidant activity and phytochemical profiling via LCMS Q-TOF - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Shafiquzzaman Siddiquee (Food Bioscience, 2024)

Karanjin: a potential furanoflavonoid for neuroprotection - Charles Gnanaraj; Mogana Govendan; Ching-Yee Loo; Yoong Soon Yong; Mahendran Sekar; Che Norma Mat Taib; Shamala Devi Subramaniam; Muhammad Dawood Shah; Wing-Hin Lee (Phytochemistry Reviews, 2024)

Phyllospheric Microorganisms and Bean Characteristics Influence Quality of Ten Genotypes of Coffea Arabica - Butian Wang; Xuedong Shi; Mengnan Shi; Meijun Qi; Zhenwei Zhang; Na Yang; Muhammad Dawood; Ahmad Naeem Shahzad; Yu Ge (Journal of Soil Science and Plant Nutrition, 2024)

Geo-statistical analysis of climatic variability and trend detection in the Hindu Kush region, North Pakistan - Muhammad Dawood; Atta-ur Rahman; Ghani Rahman; Basit Nadeem; Muhammad Miandad (Environmental Monitoring and Assessment, 2024)

Nutraceutical and Health-Promoting Potential of Lactoferrin, an Iron-Binding Protein in Human and Animal: Current Knowledge - Muhammad Faizan Ashraf; Dawood Zubair; Muhammad Noaman Bashir; Mahmoud Alagawany; Shabbir Ahmed; Qurban Ali Shah; Jameel Ahmed Buzdar; Muhammad Asif Arain (Biological Trace Element Research, 2024)

A bacterial consortium and L-tryptophan boosted glyphosate removal, mungbean growth and physiology in contaminated soil - Qammar Farooq; Muhammad Imran Khan; Muhammad Hayder Ali; Safdar Bashir; Muhammad Azam; Rashad Qadri; Basharat Ali; Muhammad Dawood; Muhammad Iftikhar Hussain (Arabian Journal of Geosciences, 2023)

Anti-arthritic effects of geranium essential oil loaded chitosan nanoparticles in Freund’s complete adjuvant induced arthritic rats through down-regulation of inflammatory cytokines - Rana Dawood Naseer; Faqir Muhammad; Bilal Aslam; Muhammad Naeem Faisal (Inflammopharmacology, 2023)

Natural and artificial green infrastructure (GI) for sustainable resilient cities: A scientometric analysis - Aqib Zahoor; Tao Xu; Miao Wang; Muhammad Dawood; Sandylove Afrane; Ying Li; Jian Lin Chen; Guozhu Mao (Environmental Impact Assessment Review, 2023)

Evaluation of phytoremediation potential and resistance of Gladiolus grandiflora L. against cadmium stress - Syed Ali Qasim Bukhari; Aamir Nawaz; Muhammad Dawood (Environmental Geochemistry and Health, 2023)

The co-application of bioslurry and compost with inorganic zinc fertilizer improved soil quality, zinc uptake, and growth of maize crop - Aqarab Husnain Gondal; Muhammad Imran Khan; Sardar Alam Cheema; Muhammad Iftikhar Hussain; Basharat Ali; Muhammad Nawaz; Muhammad Dawood; Ghulam Murtaza (Arabian Journal of Geosciences, 2023)

Assessing the potential of green CdO2 nano-catalyst for the synthesis of biodiesel using non-edible seed oil of Malabar Ebony - Sumera Arshad; Mushtaq Ahmad; Mamoona Munir; Shazia Sultana; Muhammad Zafar; Sumreen Dawood; Rozina; Ahmad M. Alghamdi; Saira Asif; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; et al. (Fuel, 2023)

Efficient application of newly synthesized green Bi2O3 nanoparticles for sustainable biodiesel production via membrane reactor - Sawaira; Mabkhoot Alsaiari; Mushtaq Ahmad; Mamoona Munir; Muhammad Zafar; Shazia Sultana; Sumreen Dawood; Abdulaziz Ibrahim Almohana; Al-Marzouki Hassan M.H; Abdulrahman Faraj Alharbi; Zubair Ahmad (Chemosphere, 2023)

Exogenous melatonin mitigates chromium toxicity in maize seedlings by modulating antioxidant system and suppresses chromium uptake and oxidative stress - Zaffar Malik; Sobia Afzal; Muhammad Dawood; Ghulam Hassan Abbasi; Muhammad Imran Khan; Muhammad Kamran; Mostafa Zhran; Malik Tahir Hayat; Muhammad Naveed Aslam; Muhammad Rafay (Environmental Geochemistry and Health, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Metal-tolerant Pantoea sp. WP-5 and organic manures enhanced root exudation and phytostabilization of cadmium in the rhizosphere of maize - Muhammad Tahir; Muhammad Bismillah Khan; Muhammad Shahid; Iftikhar Ahmad; Umaira Khalid; Muhammad Akram; Ahmad Dawood; Muhammad Kamran (Environmental Science and Pollution Research, 2022)

Spatio-temporal analysis of climatic variability, trend detection, and drought assessment in Khyber Pakhtunkhwa, Pakistan - Ghani Rahman; Atta-ur Rahman; Muhammad Mushahid Anwar; Muhammad Dawood; Muhammad Miandad (Arabian Journal of Geosciences, 2022)

Exogenous melatonin regulates chromium stress-induced feedback inhibition of photosynthesis and antioxidative protection in Brassica napus cultivars - Ahsan Ayyaz; Muhammad Ahsan Farooq; Muhammad Dawood; Abdul Majid; Muhammad Javed; Habib‐ur‐Rehman Athar; Hussan Bano; Zafar Ullah Zafar (Plant Cell Reports, 2021)

Assessing the impact of climatic change on discharge in Swat river basin using fuzzy logic model - Muhammad Dawood; Atta-ur Rahman; Shakeel Mahmood; Ghani Rahman; Shah Nazir (Arabian Journal of Geosciences, 2021)

High-resolution chemical profiling and antiparasitic potential of the tropical shrub Dillenia suffruticosa - Muhammad Dawood Shah; Kazuki Tani; Balu Alagar Venmathi Maran; Yoong Soon Yong; Ching Fui Fui; Sitti Raehanah Muhamad Shaleh; Charles S. Vairappan (Fisheries Science, 2020)

Spatio-statistical analysis of rainfall fluctuation, anomaly and trend in the Hindu Kush region using ARIMA approach - Muhammad Dawood; Atta-ur Rahman; Sami Ullah; Shakeel Mahmood; Ghani Rahman; Kamran Azam (Natural Hazards, 2020)

Use of crop growth model to simulate the impact of climate change on yield of various wheat cultivars under different agro-environmental conditions in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Ishfaq Ahmed; Muhammad Ashfaq; Dawood Jan; Shah Fahad; Xiuling Li; Depeng Wang; Muhammad Fahad; Muhammad Fayyaz; Syed Attaullah Shah (Arabian Journal of Geosciences, 2020)

Assessing the socio-economic impact of climate change on wheat production in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Dawood Jan; Muhammad Ashfaq (Environmental Science and Pollution Research, 2019)

Spatio-temporal analysis of temperature variability, trend, and magnitude in the Hindu Kush region using Monte Carlo and Sen’s slope approaches - Muhammad Dawood; Atta-ur Rahman; Sami Ullah; Ghani Rahman; Kamran Azam (Arabian Journal of Geosciences, 2018)

Spatial and temporal variation of rainfall and drought in Khyber Pakhtunkhwa Province of Pakistan during 1971–2015 - Ghani Rahman; Atta-ur-Rahman; Samiullah; Muhammad Dawood (Arabian Journal of Geosciences, 2018)

Role of brassinosteroids in alleviating toxin-induced stress of Verticillium dahliae on cotton callus growth - Noreen Bibi; Imrul Mosaddek Ahmed; Kai Fan; Muhammad Dawood; Feng Li; Shuna Yuan; Xuede Wang (Environmental Science and Pollution Research, 2017)

Spatio-statistical analysis of temperature fluctuation using Mann–Kendall and Sen’s slope approach - Atta-ur-Rahman; Muhammad Dawood (Climate Dynamics, 2017)

Leaf-based physiological, metabolic, and ultrastructural changes in cultivated cotton cultivars under cadmium stress mediated by glutathione - M. K. Daud; Lei Mei; Azizullah Azizullah; Muhammad Dawood; Imran Ali; Qaisar Mahmood; Waheed Ullah; Muhammad Jamil; S. J. Zhu (Environmental Science and Pollution Research, 2016)

Assessment of heavy metals and metalloids in tissues of two frog species: Rana tigrina and Euphlyctis cyanophlyctis from industrial city Sialkot, Pakistan - Irfan Zia Qureshi; Zeshan Kashif; Muhammad Zaffar Hashmi; Xiaomei Su; Riffat Naseem Malik; Kalim Ullah; Jinxing Hu; Muhammad Dawood (Environmental Science and Pollution Research, 2015)

Comparative study of alleviating effects of GSH, Se and Zn under combined contamination of cadmium and chromium in rice (Oryza sativa) - Fangbin Cao; Nanbo Wang; Mian Zhang; Huaxin Dai; Muhammad Dawood; Guoping Zhang; Feibo Wu (BioMetals, 2013)

Strobilanthes crispus attenuates renal carcinogen, iron nitrilotriacetate (Fe-NTA)-mediated oxidative damage of lipids and DNA - Mohammad Iqbal; Muhammad Dawood Shah; Chau Ann Lie; Chin Kim San (Molecular and Cellular Biochemistry, 2010)